Pandangan Hukum Islam Terhadap Perilaku Penyedia Jasa Endorsement Pada Sosial Media Sosial - Irwan, Islamiah; Sabir, Muhammad; Cahyani, A. Intan (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2022)
The purpose of this research is to find out the views of Islamic law on the behavior of endorsement service providers. This research uses a qualitative research type, with data collection using the library research method, the approach used is normative by studying the Qur'an and hadith as the basis of Islamic law while the data source Primary data are in the form of the Koran and Hadith, while secondary data are journal books, with deductive conclusions drawn. The results of the study show that the deviant behaviors carried out have different laws according to Islamic provisions. As for behavior such as excessive promotion and using language that is impolite and harsh, the law was originally clearly not allowed (haram), but if it is brought into the context of muamalah, the law on it may be permissible (permissible) as long as the behavior has a clear reason, such as because of elements of a promotional strategy, and as long as no one is harmed by the behavior. As for behavior such as lying, committing elements of fraud, tabarruj, and dropping other products, in the view of Islam the law is certainly not permissible (haram) because it has deviated from the provisions of Islamic sharia.